Subjective Well-being in Broken Home Individual: A Case Study in Ambon - Barsyelina Cristy Kona; Yulius Yusak Ranimpi; Simon Pieter Soegijono (Universitas Katolik Soegijapranata, 2019)
The problem and purpose of this study is to describe subjective well-being towards broken home individuals. The subjects in this study were only one criteria, who is individual were victims of divorce for more than ten years. The research method used is qualitative research with case study design. The type of qualitative approach used is descriptive phenomenology. Data collection techniques used are structured interviews and observation. Data analysis techniques used data reduction, data display, and conclusion drawing verification. Tools and materials in this study used pens, books, recording devices (tape recorder). Based on the results of the study, it can be concluded that (1) life satisfaction, (2) negative impacts, (3) expectations, (4) need fulfillment, affect subjective-well being towards broken home individuals.